A modified Maquet‐tibial tuberosity advancement technique for treatment of canine cranial cruciate ligament disease: Short term outcome and complications. Issue 1 (24th October 2017) - Retallack, Lauren M.; Daye, R. Mark
Abstract: Objective: To describe and report the outcomes of a novel modified Maquet‐tibial tuberosity advancement (mTTA) technique in dogs with naturally occurring cranial cruciate ligament (CCL) rupture, compared to a traditional tibial tuberosity advancement (tTTA) technique. Study design: Descriptive report and retrospective clinical cohort study. Sample population: Dogs (n = 70) treated via tibial tuberosity advancement (TTA). Methods: Medical records (2013‐2015) of dogs treated for CCL rupture via TTA were reviewed for: signalment, findings on physical examination, procedure (tTTA or mTTA), radiographs, complications, and outcome. Radiographs were retrospectively evaluated for patellar tendon thickness, evidence of tibial crest fractures, and implant placement. Intraoperative and postoperative complications and outcome were compared between procedures. Results: A total of 70 cases met inclusion criteria, 35 of each procedure (tTTA or mTTA). The mTTA procedure was successfully performed with good clinical and radiographic outcomes. The only difference in outcomes detected between groups is that dogs were more lame 2 weeks after tTTA than mTTA group. Conclusion: The mTTA technique represents a safe, repeatable alternative to the tTTA, with similar outcome and complication rates.